Evaluasi Kinerja Keuangan Pemerintah Desa Karangtinoto Kecamatan Rengel Kabupaten Tuban Melalui Pendekatan Value For Money - Eka Fatma Yuli Tantri; Gita Desipradani (SUSTAINABLE JURNAL AKUNTANSI, 2022)
ABSTRACTThe purpose of this study was to determine the financial performance of the Karangtinoto Village Government through the Value for Money approach. The type of data used in this research is secondary data. The results of this study indicate that the concept of measuring the performance of the Karangtinoto Village Government applies the Value for Money approach. By using this approach, the village government can measure the overall performance of public sector organizations, this will result in improved performance in the future. The performance of the Karangtinoto Village Government in 2020-2021 in terms of the economy is at an average ratio of 95.14% which indicates that this ratio is quite economical. The performance of the Karangtinoto Village Government in 2020-2021 in terms of efficiency is at an average ratio of 98.65% which indicates that this ratio is efficient. The performance of the Karangtinoto Village Government in 2020-2021 in terms of effectiveness is at an average ratio of 99.04% which indicates that this ratio is quite effective.ABSTRAKTujuan dari penelitian ini adalah untuk mengetahui kinerja keuangan Pemerintah Desa Karangtinoto melalui pendekatan Value For Money. Jenis data yang digunakan dalam penelitian ini adalah data sekunder. Hasil penelitian ini menujukkan bahwa konsep pengukuran kinerja Pemerintah Desa Karangtinoto menerapkan pendekatan Value For Money. Dengan menggunakan pendekatan ini, pemerintah desa dapat mengukur kinerja organisasi sektor publik secara menyeluruh, hal tersebut berakibat pada peningkatan kinerja dimasa yang akan datang. Kinerja Pemerintah Desa Karangtinoto di tahun 2020-2021 dari segi ekonomi berada pada rasio rata-rata 95,14% yang menunjukkan bahwa rasio ini bernilai cukup ekonomis. Kinerja Pemerintah Desa Karangtinoto di tahun 2020-2021 dari segi efisien berada pada rasio rata-rata 98,65% yang menunjukkan bahwa rasio ini bernilai efisien. Kinerja Pemerintah Desa Karangtinoto di tahun 2020-2021 dari segi efektif berada pada rasio rata-rata 99,04% yang menunjukkan bahwa rasio ini bernilai cukup efektif